The Corporate Governance Mechanism on Earnings Management and Firm Performance - Ilham Maulana; Bambang Haryadi; Mohammad Arief (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2022)
Corporate governance mechanism is a form of supervision of the company to run effectively and efficiently to improve firm performance and value. The supervision that corporate governance mechanism provide is to lesser the agency conflicts due the different interest between manager and owner such earnings management that is detrimental to shareholders. This study examines corporate governance as a supervisory mechanism that aims to improve firm performance, value and minimize earnings management. Then, we analyze the possibility that corporate governance mechanisms can improve firm’s performance and value by controlling earnings management. Using data of banking companies from 2018-2019 then tested using partial least squares with the WarpPLS application, we found evidence that corporate governance mechanisms positively influence the company's financial performance. Corporate governance mechanism has a negative effect on firm value. Corporate governance mechanisms have a negative effect on earnings management. Then earnings management does not provide a mediating effect in the relationship of corporate governance with the company's financial performance and firm value.